A high-strength aggregate made of high-content coal gasification slag and all-solid waste and its preparation method

By preparing high-strength aggregates made from gasification slag with a high content of solid waste, using materials such as gasification slag powder, fly ash, red mud and modified ceramic fiber, combined with high-temperature calcination and granulation technology, the problems of long preparation time and low strength of gasification slag are solved, and efficient solid waste utilization and aggregate strength improvement are achieved.

CN120463486BActive Publication Date: 2025-09-05ORDOS INST OF APPLIED TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202510970736.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-15
Publication Date
2025-09-05
Estimated Expiration
2045-07-15

AI Technical Summary

Technical Problem

The solid waste aggregate prepared from coal gasification slag in the prior art has a long process time and low strength, and the existing ceramsite preparation consumes a lot of energy and the product strength is not high.

Method used

Using coal gasification slag powder, fly ash, red mud and modified ceramic fiber and other materials, high-strength aggregate with high content of coal gasification slag solid waste is prepared through ball milling, granulation and high-temperature calcination. Solid waste emulsion is used as a binder, combined with sodium silicate solution and modified ceramic fiber to improve the adhesion and structural integrity.

Benefits of technology

It realizes the large-scale comprehensive utilization of solid waste, improves the cylinder compressive strength and apparent density of aggregate, reduces porosity, solves the problems of long preparation process and low strength, and avoids environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120463486B_ABST
    Figure CN120463486B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of building material concrete aggregate, and in particular to a high-strength aggregate made of all-solid waste from coal gasification slag with a high content and a preparation method thereof. Calculated by weight, the high-strength aggregate made of all-solid waste from coal gasification slag with a high content comprises 40 to 60 parts of coal gasification slag powder, 40 to 60 parts of fly ash, 6 to 12 parts of red mud, 3 to 5 parts of modified ceramic fiber, and solid waste emulsion. The mass of the solid waste emulsion is 4 to 5% of the total mass of the coal gasification slag powder, fly ash, red mud, and modified ceramic fiber; the preparation method of the solid waste emulsion comprises: crushing the red mud and straw through a 150-mesh sieve to obtain fine powder; mixing the fine powder with water in a mass-to-volume ratio of 1: (1 to 2), and then adding a water reducer and stirring to obtain a solid waste emulsion. The present application provides a high-strength aggregate made of all-solid waste from coal gasification slag with a high content and a preparation method thereof, in order to solve the problems of a long preparation process and low strength of solid waste aggregates in related technologies.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of building material concrete aggregates, and in particular to a high-strength aggregate made of high-content coal gasification slag and all-solid waste and a preparation method thereof. Background Art

[0002] With the rapid development of coal gasification technology, the production of its byproduct, coal gasification slag, has also increased dramatically. Currently, the primary method of treating coal gasification slag is through stockpiling. However, this fine slag has a high moisture content, resulting in the continuous leakage of black water during storage. Furthermore, the fine slag is highly corrosive, causing water, soil, and air pollution and becoming a major factor in causing environmental and safety issues. Therefore, the efficient disposal and utilization of coal gasification slag is an essential requirement for promoting the green and high-quality development of solid waste materials.

[0003] The output of ready-mixed concrete in Inner Mongolia Autonomous Region will be 32 million m3 in 2023. 3 The use of aggregates is enormous. Currently, the primary aggregates used in civil engineering are still natural aggregates (pebbles, crushed stone, river sand, etc.). After decades of extensive mining, natural aggregate resources are rapidly decreasing, and in some areas, natural aggregates are nearly depleted. The development and utilization of aggregate resources present numerous challenges. Using solid waste to prepare aggregates can facilitate the large-scale utilization of solid waste, while generating positive social and environmental benefits and considerable economic benefits.

[0004] In the related art, there is an application of using gasification slag as solid waste material to prepare ceramsite, but most of the time, additives are used, energy consumption is high and the strength of the product is not high. For example, patent CN117800753A discloses a gasification slag composite ceramsite and its preparation method. The preparation temperature of the ceramsite needs to be between 90 and 150°C, the calcination temperature is between 1200 and 1400°C, and the final ceramsite cylinder compressive strength is low, reaching only 6.3MPa; while unfired ceramsite takes a long time, usually more than a week. Summary of the Invention

[0005] The present application provides a high-strength aggregate made of all-solid waste with a high content of coal gasification slag and a preparation method thereof, so as to solve the problems of long preparation process and low strength of solid waste aggregate in related technologies.

[0006] In a first aspect, a high-strength aggregate made of high-content coal gasification slag and all-solid waste is provided, which comprises, by weight:

[0007] 40-60 parts of coal gasification slag powder, 40-60 parts of fly ash, 6-12 parts of red mud, 3-5 parts of modified ceramic fiber, and solid waste emulsion, where the mass of the solid waste emulsion is 4-5% of the total mass of the coal gasification slag powder, fly ash, red mud, and modified ceramic fiber;

[0008] The preparation method of the solid waste emulsion comprises the following steps:

[0009] The red mud and straw were crushed through a 150-mesh sieve to obtain fine powder, wherein the mass ratio of the red mud to the straw was 1:(2-4);

[0010] The micropowder and water are mixed in a mass-to-volume ratio of 1:(1-2), and then a water reducer is added and stirred to obtain a solid waste emulsion, wherein the mass ratio of the water reducer to red mud is 1:(30-50).

[0011] Preferably, the method for preparing the modified ceramic fiber comprises the following steps:

[0012] Sodium carbonate and potassium dihydrogen phosphate are mixed in a mass ratio of 8:(5-6) to obtain a mixture, and the mixture is dissolved in deionized water in a mass volume ratio of 1:20 to obtain a modified solution;

[0013] The ceramic fiber and the modified solution are mixed in a mass-to-volume ratio of 1:(5-10), immersed for 2-4 hours, and then filtered to obtain the modified ceramic fiber.

[0014] Preferably, the water reducer is one of sodium lignin sulfonate and calcium lignin sulfonate.

[0015] In a second aspect, a method for preparing high-strength aggregate made from high-content coal gasification slag and all-solid waste is provided, which is used to prepare a high-strength aggregate made from high-content coal gasification slag and all-solid waste as described above, characterized in that it comprises the following steps:

[0016] S1. Grind the coal gasification slag in a ball mill for 30-60 min, and then pass through a 0.15 mm sieve to obtain coal gasification slag powder;

[0017] S2. Mixing 40-60 parts of the coal gasification slag powder with 40-60 parts of fly ash, 6-12 parts of red mud, and 3-5 parts of modified ceramic fiber to obtain a mixture;

[0018] S3, the compound is mixed with the solid waste emulsion, and put into a disc granulator for granulation, the granulator speed is made to be 50-60r / min, and 1wt% of sodium silicate solution is sprayed, after obtaining 5mm balls in the granulator, the sodium silicate solution is stopped, and the granulator speed is adjusted to 90-110r / min, and granulation is continued to obtain raw balls with a particle size of 9-13mm;

[0019] S4, drying the raw balls at 105° C. for 4 hours to obtain dried raw balls;

[0020] S5. Place the dried raw material balls into a high-temperature box furnace for calcination:

[0021] S501, setting the temperature of the high-temperature box furnace to 600°C, and preheating the dried raw balls at 600°C for 60 minutes;

[0022] S502, adjusting the temperature of the high-temperature box furnace to 1000-1100° C. and calcining for 30 minutes to complete the calcination;

[0023] S6. After the temperature inside the high-temperature box furnace drops below 500°C, the aggregate is taken out and cooled naturally. After cooling to room temperature, a high-strength aggregate made of high-content coal gasification slag and all-solid waste is obtained.

[0024] Preferably, in S501, when the high-temperature box furnace is heated to a preheating temperature of 600°C, the heating rate is 10°C / min.

[0025] Preferably, in S502, when the high temperature box furnace is raised to 1000-1100°C, the heating rate is 5°C / min.

[0026] The beneficial effects of the technical solution provided by this application include:

[0027] The present application provides a high-strength aggregate made of high-content coal gasification slag and all-solid waste and a preparation method thereof. Coal gasification slag, fly ash, red mud, ceramic fiber and straw are applied to the preparation of aggregate, which can realize large-scale comprehensive utilization of industrial solid waste and reduce environmental pollution caused by solid waste accumulation; ceramic fiber plays a bridging role, and on the premise that it has high tensile strength itself, it can bear part of the tensile force when dispersed in the aggregate, effectively improving the ability of the aggregate to resist pressure damage and improving the cylinder compressive strength; red mud and straw are prepared into a solid waste emulsion, which is used as a binder to improve the adhesion of the raw materials during the granulation of the aggregate, thereby ensuring the integrity of the aggregate structure; the adhesive material formed after drying fills part of the pores of the aggregate, effectively reducing the porosity, increasing the apparent density, and further enhancing the cylinder compressive strength of the aggregate. The raw materials of the aggregate are all solid waste, and the preparation method is simple. Therefore, it can solve the problems of long preparation process and low strength of solid waste aggregate in related technologies. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without any creative work.

[0029] Figure 1 Flow chart of the method for preparing high-strength aggregate from all-solid waste with high content of coal gasification slag provided in this application;

[0030] Figure 2 This is a scanning electron microscope image of the mixed material before calcination in Example 7 provided in this application;

[0031] Figure 3This is a scanning electron microscope image of the aggregate obtained in Example 7 provided in this application;

[0032] Figure 4 This is a scanning electron microscope image of the aggregate obtained in Comparative Example 1 provided in this application;

[0033] Figure 5 This is a scanning electron microscope image of the aggregate obtained in Comparative Example 2 provided in this application;

[0034] Figure 6 XDR images of the aggregates obtained in Examples 1 to 4 provided in this application;

[0035] Figure 7 This is the XDR image of the aggregate obtained in Examples 5 and 6 provided in this application;

[0036] Figure 8 The XDR diagram of the aggregate obtained in Example 7 provided in this application, the left diagram is the XDR diagram of the aggregate obtained in Example 7 before calcination, and the right diagram is the XDR diagram of the aggregate obtained in Example 7 after calcination;

[0037] Figure 9 XDR images of the aggregates obtained in Comparative Examples 1 to 4 provided in this application;

[0038] Figure 10 This is the XDR diagram of the aggregate obtained in Comparative Examples 5 and 6 provided in this application. DETAILED DESCRIPTION

[0039] To make the purpose, technical solutions, and advantages of the embodiments of this application more clear, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the drawings in the embodiments of this application. Obviously, the described embodiments are part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of this application.

[0040] See also Figures 1 to 10 As shown, the present application provides a high-strength aggregate made of all-solid waste with a high content of coal gasification slag (hereinafter referred to as "aggregate"), which can solve the problems of long preparation process and low strength of solid waste aggregate in related technologies.

[0041] Specifically, the high-strength aggregate made of high-content coal gasification slag and all-solid waste includes 40-60 parts of coal gasification slag powder, 40-60 parts of fly ash, 6-12 parts of red mud, 3-5 parts of modified ceramic fiber, and solid waste emulsion. The mass of the solid waste emulsion is 4-5% of the total mass of the coal gasification slag powder, fly ash, red mud, and modified ceramic fiber.

[0042] The method for preparing high-strength aggregate made of high-content coal gasification slag and all-solid waste comprises the following steps:

[0043] S1. Grind the coal gasification slag in a ball mill for 30-60 min, and then pass through a 0.15 mm sieve to obtain coal gasification slag powder;

[0044] S2. Mixing 40-60 parts of the coal gasification slag powder with 40-60 parts of fly ash, 6-12 parts of red mud, and 3-5 parts of modified ceramic fiber to obtain a mixture;

[0045] The preparation method of the modified ceramic fiber comprises the following steps:

[0046] Sodium carbonate and potassium dihydrogen phosphate are mixed in a mass ratio of 8:(5-6) to obtain a mixture, and the mixture is dissolved in deionized water in a mass volume ratio of 1:20 to obtain a modified solution;

[0047] The ceramic fiber and the modified solution are mixed in a mass-to-volume ratio of 1:(5-10), immersed for 2-4 hours, and then filtered to obtain the modified ceramic fiber.

[0048] S3, the mixture is mixed with the solid waste emulsion, and put into a disc granulator for granulation, the granulator speed is set to 50-60 r / min, and 1 wt% sodium silicate solution is sprayed. After 5 mm balls are obtained in the granulator, spraying of the sodium silicate solution is stopped, the granulator speed is adjusted to 90-110 r / min, and granulation is continued to obtain raw material balls with a particle size of 9-13 mm. The mass of the solid waste emulsion is 4-5% of the mass of the mixture.

[0049] The particle size of the raw material balls is controlled at 9~13mm, that is, the raw material balls within this particle size range are used for calcination to prepare aggregate.

[0050] The method for preparing the solid waste emulsion comprises the following steps:

[0051] The red mud and straw were crushed through a 150-mesh sieve to obtain fine powder, wherein the mass ratio of the red mud to the straw was 1:(2-4);

[0052] The micropowder and water are mixed in a mass-to-volume ratio of 1:(1-2), and then a water reducer is added and stirred to obtain a solid waste emulsion, wherein the mass ratio of the water reducer to red mud is 1:(30-50).

[0053] In some embodiments, the water reducing agent is one of sodium lignin sulfonate and calcium lignin sulfonate.

[0054] S4, drying the raw balls at 105° C. for 4 hours to obtain dried raw balls, so as to avoid surface cracking caused by the rapid increase in temperature due to moisture in the aggregate during the calcination process;

[0055] S5. Place the dried raw material balls into a high-temperature box furnace for calcination:

[0056] S501, setting the temperature of the high-temperature box furnace to 600°C, and preheating the dried raw balls at 600°C for 60 minutes;

[0057] In some embodiments, when the high temperature box furnace is heated to a preheating temperature of 600° C., the heating rate is 10° C. / min.

[0058] S502, adjusting the temperature of the high-temperature box furnace to 1000-1100° C. and calcining for 30 minutes to complete the calcination;

[0059] In some embodiments, when the high temperature box furnace is heated to 1000-1100° C., the heating rate is 5° C. / min.

[0060] S6. After the temperature inside the high-temperature box furnace drops below 500°C, the aggregate is taken out and cooled naturally. After cooling to room temperature, a high-strength aggregate made of high-content coal gasification slag and all-solid waste is obtained.

[0061] During the firing process of the aggregate, reactions such as decomposition, melting and crystallization occurred. During the preheating process (room temperature ~ 600℃), the internal phase of the aggregate did not change significantly, and the phase in the raw materials was still the main phase. During the calcination process, at 600~900℃, the silicon oxide, aluminum oxide and calcium oxide in the raw materials participated in the solid-phase reaction to generate albite (accounting for more than 40%) and diopside (accounting for more than 40%); as the temperature continued to rise, diopside rapidly dissolved in the alkali metal aluminosilicate flux in the range of 1000~1100℃, which on the one hand could precipitate new feldspar crystals, and on the other hand promoted the melting of free quartz in the blank. Ultimately, the amount of residual quartz in the aggregate was reduced, and the strength and thermal stability were improved. At 1100℃, the main crystal phase of the aggregate was albite (accounting for about 60%), and contained some diopside and a small amount of quartz, calcite and other mineral phases.

[0062] Example 1

[0063] The high-strength aggregate made of high-content coal gasification slag and all-solid waste provided in this embodiment includes 300g of coal gasification slag powder, 200g of fly ash, 30g of red mud, 12g of modified ceramic fiber and 27g of solid waste emulsion.

[0064] The preparation method comprises the following steps:

[0065] S1. Grind the coal gasification slag in a ball mill for 30 min and pass it through a 0.15 mm sieve to obtain coal gasification slag powder;

[0066] S2. Mixing 300 g of the coal gasification slag powder with 200 g of fly ash, 30 g of red mud, and 12 g of modified ceramic fiber to obtain a mixture. The preparation method of the modified ceramic fiber comprises the following steps:

[0067] Dissolve 8 g of sodium carbonate and 6 g of potassium dihydrogen phosphate in 280 mL of deionized water to obtain a modified solution;

[0068] 12 g of ceramic fiber was mixed with 120 mL of the modified solution, immersed for 2 h, and then filtered to obtain the modified ceramic fiber.

[0069] S3. Mix 542 g of the mixed material obtained in S2 with 28 g of the solid waste emulsion, and put them into a disc granulator for granulation. First, set the granulator speed to 50 r / min and spray 1 wt% sodium silicate solution. After 5 mm small balls are obtained in the granulator, stop spraying the sodium silicate solution, adjust the granulator speed to 90 r / min, and continue granulation to obtain raw balls with a particle size of 9-13 mm.

[0070] The preparation method of the solid waste emulsion comprises the following steps:

[0071] 10 g of red mud and 40 g of straw were crushed through a 150-mesh sieve to obtain fine powder;

[0072] The micropowder was mixed with 50 mL of water, and 0.2 g of sodium lignin sulfonate was added and stirred to obtain a solid waste emulsion.

[0073] S4, drying the raw balls at 105° C. for 4 hours to obtain dried raw balls;

[0074] S5. Place the dried raw material balls into a high-temperature box furnace for calcination:

[0075] S501, setting the temperature of the high-temperature box furnace to 600°C, and preheating the dried raw balls at 600°C for 60 minutes;

[0076] S502, adjusting the temperature of the high-temperature box furnace to 1000° C. and calcining for 30 minutes to complete the calcination;

[0077] S6. After the temperature inside the high-temperature box furnace drops below 500°C, the aggregate is taken out and cooled naturally. After cooling to room temperature, a high-strength aggregate made of high-content coal gasification slag and all-solid waste is obtained.

[0078] Example 2

[0079] The high-strength aggregate made of high-content coal gasification slag and all-solid waste provided in this embodiment includes 300g of coal gasification slag powder, 200g of fly ash, 60g of red mud, 25g of modified ceramic fiber and 24g of solid waste emulsion.

[0080] The preparation method comprises the following steps:

[0081] S1. Grind the coal gasification slag in a ball mill for 30 min and pass it through a 0.15 mm sieve to obtain coal gasification slag powder;

[0082] S2. Mixing 300 g of the coal gasification slag powder with 200 g of fly ash, 60 g of red mud, and 25 g of modified ceramic fiber to obtain a mixture. The preparation method of the modified ceramic fiber comprises the following steps:

[0083] Dissolve 8 g of sodium carbonate and 5 g of potassium dihydrogen phosphate in 260 mL of deionized water to obtain a modified solution;

[0084] 25 g of ceramic fiber was mixed with 250 mL of the modified solution, immersed for 4 h, and then filtered to obtain the modified ceramic fiber.

[0085] S3. Mix 585 g of the mixture obtained in S2 with 24 g of the solid waste emulsion, and put them into a disc granulator for granulation. First, set the granulator speed to 60 r / min and spray 1 wt% sodium silicate solution. After obtaining 5 mm small balls in the granulator, stop spraying the sodium silicate solution, adjust the granulator speed to 110 r / min, and continue granulation to obtain raw balls with a particle size of 9 to 13 mm.

[0086] The preparation method of the solid waste emulsion comprises the following steps:

[0087] 20 g of red mud and 40 g of straw were crushed through a 150-mesh sieve to obtain fine powder;

[0088] The micropowder was mixed with 60 mL of water, and 0.5 g of sodium lignin sulfonate was added and stirred to obtain a solid waste emulsion.

[0089] S4, drying the raw balls at 105° C. for 4 hours to obtain dried raw balls;

[0090] S5. Place the dried raw material balls into a high-temperature box furnace for calcination:

[0091] S501, setting the temperature of the high-temperature box furnace to 600°C, and preheating the dried raw pellets at 600°C for 60 minutes, and when the high-temperature box furnace is heated from room temperature to the preheating temperature of 600°C, the heating rate is 10°C / min;

[0092] S502, adjusting the temperature of the high-temperature box furnace to 1050° C. and calcining for 30 minutes to complete the calcination;

[0093] S6. After the temperature inside the high-temperature box furnace drops below 500°C, the aggregate is taken out and cooled naturally. After cooling to room temperature, a high-strength aggregate made of high-content coal gasification slag and all-solid waste is obtained.

[0094] Example 3

[0095] The difference from Example 2 is that the calcination temperature in this example is 1100°C.

[0096] Example 4

[0097] The high-strength aggregate made of high-content coal gasification slag and all-solid waste provided in this embodiment includes 200g of coal gasification slag powder, 200g of fly ash, 32g of red mud, 12g of modified ceramic fiber and 20g of solid waste emulsion.

[0098] The preparation method comprises the following steps:

[0099] S1. Grind the coal gasification slag in a ball mill for 30 min and pass it through a 0.15 mm sieve to obtain coal gasification slag powder;

[0100] S2. Mixing 200 g of the coal gasification slag powder with 200 g of fly ash, 32 g of red mud, and 12 g of modified ceramic fiber to obtain a mixture. The preparation method of the modified ceramic fiber comprises the following steps:

[0101] Dissolve 8 g of sodium carbonate and 5.5 g of potassium dihydrogen phosphate in 270 mL of deionized water to obtain a modified solution;

[0102] 12 g of ceramic fiber was mixed with 120 mL of the modified solution, immersed for 3 h, and then filtered to obtain the modified ceramic fiber.

[0103] S3. Mix 444 g of the mixture obtained in S2 with 20 g of the solid waste emulsion, and put them into a disc granulator for granulation. First, set the granulator speed to 55 r / min and spray 1 wt% sodium silicate solution. After obtaining 5 mm balls in the granulator, stop spraying the sodium silicate solution, adjust the granulator speed to 100 r / min, and continue granulation to obtain raw balls with a particle size of 9 to 13 mm.

[0104] The preparation method of the solid waste emulsion comprises the following steps:

[0105] 9 g of red mud and 27 g of straw were crushed through a 150-mesh sieve to obtain fine powder;

[0106] The micropowder was mixed with 40 mL of water, and 0.3 g of sodium calcium lignin sulfonate was added and stirred to obtain a solid waste emulsion.

[0107] S4, drying the raw balls at 105° C. for 4 hours to obtain dried raw balls;

[0108] S5. Place the dried raw material balls into a high-temperature box furnace for calcination:

[0109] S501, setting the temperature of the high-temperature box furnace to 600°C, and preheating the dried raw balls at 600°C for 60 minutes;

[0110] S502, adjusting the temperature of the high-temperature box furnace to 1000° C. and calcining for 30 minutes to complete the calcination;

[0111] S6. After the temperature inside the high-temperature box furnace drops below 500°C, the aggregate is taken out and cooled naturally. After cooling to room temperature, a high-strength aggregate made of high-content coal gasification slag and all-solid waste is obtained.

[0112] Example 5

[0113] The difference from Example 4 is that the calcination temperature in S502 is adjusted to 1050°C.

[0114] Example 6

[0115] The difference from Example 4 is that the calcination temperature in S502 is adjusted to 1100°C.

[0116] Example 7

[0117] The high-strength aggregate made of high-content coal gasification slag and all-solid waste provided in this embodiment includes 200g of coal gasification slag powder, 300g of fly ash, 40g of red mud, 15g of modified ceramic fiber and 25g of solid waste emulsion.

[0118] The preparation method comprises the following steps:

[0119] S1. Grind the coal gasification slag in a ball mill for 50 min and pass it through a 0.15 mm sieve to obtain coal gasification slag powder;

[0120] S2. Mixing 200 g of the coal gasification slag powder with 300 g of fly ash, 40 g of red mud, and 15 g of modified ceramic fiber to obtain a mixture. The preparation method of the modified ceramic fiber comprises the following steps:

[0121] Dissolve 8 g of sodium carbonate and 5.5 g of potassium dihydrogen phosphate in 270 mL of deionized water to obtain a modified solution;

[0122] 15 g of ceramic fiber was mixed with 150 mL of the modified solution, immersed for 3 h, and then filtered to obtain the modified ceramic fiber.

[0123] S3. Mix 555 g of the mixture obtained in S2 with 25 g of the solid waste emulsion, and put them into a disc granulator for granulation. First, set the granulator speed to 50 r / min and spray 1 wt% sodium silicate solution. After obtaining 5 mm small balls in the granulator, stop spraying the sodium silicate solution, adjust the granulator speed to 110 r / min, and continue granulation to obtain raw balls with a particle size of 9-13 mm.

[0124] The preparation method of the solid waste emulsion comprises the following steps:

[0125] 12 g of red mud and 36 g of straw were crushed through a 150-mesh sieve to obtain fine powder;

[0126] The micropowder was mixed with 50 mL of water, and 0.4 g of sodium lignin sulfonate was added and stirred to obtain a solid waste emulsion.

[0127] S4, drying the raw balls at 105° C. for 4 hours to obtain dried raw balls;

[0128] S5. Place the dried raw material balls into a high-temperature box furnace for calcination:

[0129] S501, setting the temperature of the high-temperature box furnace to 600°C, heating from room temperature to 600°C at a heating rate of 10°C / min, and preheating the dried raw balls at 600°C for 60 minutes;

[0130] S502, adjusting the temperature of the high-temperature box furnace to 1100° C. and calcining for 30 minutes to complete the calcination, wherein the heating rate is 5° C. / min when increasing from the preheating temperature of 600° C. to the calcination temperature;

[0131] S6. After the temperature inside the high-temperature box furnace drops below 500°C, the aggregate is taken out and cooled naturally. After cooling to room temperature, a high-strength aggregate made of high-content coal gasification slag and all-solid waste is obtained.

[0132] Comparative Example 1

[0133] The difference between this comparative example and Example 7 is that the calcination step is not performed in this comparative example, that is, only S501 is performed in S5, and S502 is not performed.

[0134] Comparative Example 2

[0135] The difference between this comparative example and Example 7 is that the preheating step is not performed in this comparative example, that is, only S502 is performed in S5, and S501 is not performed.

[0136] Comparative Example 3

[0137] The difference from Example 7 is that the calcination temperature in this comparative example S502 is 900°C.

[0138] Comparative Example 4

[0139] The difference between this comparative example and Example 7 is that this comparative example does not use solid waste emulsion, that is, in the preparation method, the solid waste emulsion in S3 is replaced by an equal amount of water.

[0140] Comparative Example 5

[0141] The difference from Example 7 is that this comparative example does not use red mud in S2 of the preparation method.

[0142] Comparative Example 6

[0143] The difference between this comparative example and Example 7 is that this comparative example does not use modified ceramic fiber.

[0144] The specific raw material ratios and calcination parameters of Examples 1 to 7 and Comparative Examples 1 to 6 are shown in Table 1.

[0145] Table 1 Raw material ratios and calcination parameters of Examples and Comparative Examples

[0146]

[0147] The aggregates obtained in Examples 1 to 7 and Comparative Examples 1 to 6 were tested using the test methods for bulk density, apparent density, cylinder compressive strength, and water absorption in GB / T 17431.2-2010. The test results for bulk density, apparent density, cylinder compressive strength, and water absorption are shown in Table 2.

[0148] Table 2 Performance test results of aggregates obtained in Examples and Comparative Examples

[0149]

[0150] It should be noted that the aggregate prepared in Comparative Example 1 has poor formability, so its bulk density, apparent density, cylinder compressive strength and water absorption were not tested.

[0151] See also Figures 2 to 5 As shown in FIG, and in combination with the parameter comparison of Example 7 with Comparative Examples 1 and 2, it can be seen that preheating and calcining make the internal crystal conversion of the aggregate more complete, increase the bulk density and apparent density, and improve the cylinder compressive strength of the aggregate; see Figures 6 to 10 ,Through the XRD patterns of the aggregates obtained in the examples and comparative examples, we can see the evolution of pore volume and crystallinity. The porosity of Example 7 is significantly reduced (it should be noted that, Figures 6 to 10 Labradorite is labradorite, Diopside is diopside, and Hematite is hematite).

[0152] From the comparison between Example 4 and Example 5, it can be seen that the increase of calcination temperature can effectively increase the cylinder compressive strength of the aggregate: after the calcination temperature is increased from 1000°C to 1100°C, the cylinder compressive strength increases by 5.4 MPa.

[0153] From the comparison between Example 7 and Comparative Example 4, it can be seen that the straw biomass in the solid waste emulsion is carbonized, and the carbonaceous structure is tightly combined with the coal gasification slag, which improves the binding degree of the aggregate, specifically manifested in a significant increase in bulk density, apparent density, and cylinder compressive strength;

[0154] From the comparison between Example 7 and Comparative Example 5, it can be seen that the addition of red mud has a certain effect on the strength of the aggregate.

[0155] Specifically, the bulk density and apparent density of Comparative Examples 4 and 5 are higher than those of Example 4, indicating that in the water-free or red mud-free system, the particles are mainly physically stacked with high density, but there is no emulsion and gel connection, and they are only stacked by gravity, so the cylinder pressure strength is insufficient; in Example 7, red mud and modified ceramic fibers are combined, the ratio of heavy and light materials is relatively balanced, the emulsion plays a gelling role and fills the pores to form a reinforced structure; Comparative Example 6 lacks modified ceramic fibers compared to Example 7 and has a higher bulk density, indicating that the steric hindrance effect of the modified ceramic fibers reduces the compactness of the stacking, but introduces uniform pores, which is beneficial to the improvement of the cylinder pressure strength and the balance between water absorption rate.

[0156] The red mud in Examples 1 and 2 has a high specific gravity, which will form glassy phase pores after calcination, thereby reducing the cylinder pressure strength. At the same time, the high porosity also leads to an increase in water absorption. Comparative Example 2 was not preheated, and pores were generated due to the rapid evaporation of water at the calcination temperature, resulting in an increase in water absorption. Comparative Example 3 has a lower calcination temperature than Example 7, and the solid-phase reaction is insufficient, so the cylinder pressure strength is also lower.

[0157] The foregoing is merely a list of specific embodiments of the present application, intended to enable those skilled in the art to understand or implement the present application. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present application. Therefore, the present application is not limited to the embodiments shown herein, but is intended to conform to the broadest scope consistent with the principles and novel features of the present application.

Claims

1. A high-strength aggregate made from high-content coal gasification slag and solid waste, characterized in that: In parts by mass, it includes: 40-60 parts of coal gasification slag powder, 40-60 parts of fly ash, 6-12 parts of red mud, 3-5 parts of modified ceramic fiber, solid waste emulsion; The mass of the solid waste emulsion is 4-5% of the total mass of coal gasification slag powder, fly ash, red mud and modified ceramic fiber; The preparation method of the solid waste emulsion comprises the following steps: The red mud and straw were crushed through a 150-mesh sieve to obtain fine powder, wherein the mass ratio of the red mud to the straw was 1:(2-4); The micropowder and water are mixed in a mass-to-volume ratio of 1:(1-2), and then a water reducer is added and stirred to obtain a solid waste emulsion, wherein the mass ratio of the water reducer to red mud is 1:(30-50).

2. The high-strength aggregate made of high-content coal gasification slag and all-solid waste according to claim 1, characterized in that: The preparation method of the modified ceramic fiber comprises the following steps: Sodium carbonate and potassium dihydrogen phosphate are mixed in a mass ratio of 8:(5-6) to obtain a mixture, and the mixture is dissolved in deionized water in a mass volume ratio of 1:20 to obtain a modified solution; The ceramic fiber and the modified solution are mixed in a mass-to-volume ratio of 1:(5-10), immersed for 2-4 hours, and then filtered to obtain the modified ceramic fiber.

3. The high-strength aggregate made from high-content coal gasification slag and all-solid waste according to claim 1, characterized in that: The water reducer is one of sodium lignin sulfonate and calcium lignin sulfonate.

4. A method for preparing high-strength aggregate made from high-content coal gasification slag and all-solid waste, which is used to prepare a high-strength aggregate made from high-content coal gasification slag and all-solid waste as claimed in any one of claims 1 to 3, characterized in that: It includes the following steps: S1. Grind the coal gasification slag in a ball mill for 30-60 min, and then pass through a 0.15 mm sieve to obtain coal gasification slag powder; S2. Mixing 40-60 parts of the coal gasification slag powder with 40-60 parts of fly ash, 6-12 parts of red mud, and 3-5 parts of modified ceramic fiber to obtain a mixture; S3, the compound is mixed with the solid waste emulsion, and put into a disc granulator for granulation, the granulator speed is made to be 50-60r / min, and 1wt% of sodium silicate solution is sprayed, after obtaining 5mm balls in the granulator, the sodium silicate solution is stopped, and the granulator speed is adjusted to 90-110r / min, and granulation is continued to obtain raw balls with a particle size of 9-13mm; S4, drying the raw balls at 105° C. for 4 hours to obtain dried raw balls; S5. Place the dried raw material balls into a high-temperature box furnace for calcination: S501, setting the temperature of the high-temperature box furnace to 600°C, and preheating the dried raw balls at 600°C for 60 minutes; S502, adjusting the temperature of the high-temperature box furnace to 1000-1100° C. and calcining for 30 minutes to complete the calcination; S6. After the temperature inside the high-temperature box furnace drops below 500°C, the aggregate is taken out and cooled naturally. After cooling to room temperature, a high-strength aggregate made of high-content coal gasification slag and all-solid waste is obtained.

5. The method for preparing high-strength aggregate from high-content coal gasification slag and all-solid waste according to claim 4, characterized in that: In S501, when the high temperature box furnace is heated to a preheating temperature of 600°C, the heating rate is 10°C / min.

6. The method for preparing high-strength aggregate from high-content coal gasification slag and all-solid waste according to claim 4, characterized in that: In S502, when the high temperature box furnace is raised to 1000-1100°C, the heating rate is 5°C / min.

Citation Information

Patent Citations

  • Preparation method of lightweight high-strength ceramsite, prepared lightweight high-strength ceramsite and application

    CN112430062A

  • Preparation method of high-content coal gasification coarse slag lightweight high-strength ceramsite

    CN116693323A